2014
DOI: 10.4236/fns.2014.522229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Tea Consumption on Selected Metabolic Biomarkers in Asian Indian Women with Metabolic Syndrome

Abstract: Evidence for benefits of anti-oxidative power of polyphenols in cardiovascular diseases has been established. In the present study, effect of polyphenol rich green tea on selected metabolic biomarkers among Asian Indian women with metabolic syndrome in normal free living condition has been recorded. Thirty three Asian Indian women (>30 y) confirmed as having metabolic syndrome, were enrolled for the present study based on written informed consent. Subjects were asked to consume three cups of green tea daily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…p2 obtained by independent t-test for comparing the differences between green tea and control groups and <0.05 is considered significant. MET = metabolic equivalent of task; MUFA = mono unsaturated fatty acid; PUFA = polyunsaturated fatty acid; SFA = saturated fatty acid Effect of green tea consumption have also reported a significant reduction in plasma TC, which could be due to longer intervention or higher doses of green tea consumed in these studies, as compared to ours (Ray and Singhania, 2014;Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…p2 obtained by independent t-test for comparing the differences between green tea and control groups and <0.05 is considered significant. MET = metabolic equivalent of task; MUFA = mono unsaturated fatty acid; PUFA = polyunsaturated fatty acid; SFA = saturated fatty acid Effect of green tea consumption have also reported a significant reduction in plasma TC, which could be due to longer intervention or higher doses of green tea consumed in these studies, as compared to ours (Ray and Singhania, 2014;Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 68%
“…In a study by Wang et al (2010) on the effects of GTCs on body composition, it was observed that three-month consumption of green tea extract caused a significant decrease in abdominal fat, waist circumference (WC) and body weight in overweight individuals. "A four-month consumption of green tea in a study of" Ray and Singhania (2014) "and a three-month consumption of green tea extract containing epigallocatechin gallate (EGCG) in a study of " Chen et al (2016) caused a significant reduction in weight, WC, plasma LDL levels and total cholesterol (TC) in women with abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the MeS patients in this study, FSG and HbA1c levels were similar at baseline of the study which is similar to other studies. 17,19 After consumption of green tea, the mean FSG and HbA1c significantly decreased from their baseline as well as it was found lower to the control group after 12 weeks. These findings were supported by others.…”
Section: Discussionmentioning
confidence: 92%
“…These findings were supported by others. 13,19 On the contrary, one study found significant reduction in HbA1c level with a non-significant change in FSG level and the duration of intervention was short (8 weeks). 12 Another study found no significant difference in FSG and HbA1c level.…”
Section: Discussionmentioning
confidence: 97%